Denervation findings on EMG in amyotrophic lateral sclerosis and correlation with prognostic milestones: Data from a retrospective study. Issue 8 (August 2020) - Fileccia, E.; De Pasqua, S.; Rizzo, G.; Di Stasi, V.; Vacchiano, V.; Avoni, P.; Bartolomei, I.; Pastorelli, F.; Plasmati, R.; Donadio, V.; Salvi, F.; Liguori, R.; et al.
Highlights: EMG examination is important not just for diagnosis of ALS but also for its intrinsic prognostic value. Denervation potentials can predict ventilatory dysfunction and survival in ALS. The prognostic value of EMG is independent from the clinical phenotype of the patient. Abstract: Objective: To verify whether the finding of denervation activity on EMG at the time of diagnosis has a prognostic value in amyotrophic lateral sclerosis (ALS). Methods: We retrospectively studied all the patients discharged with a diagnosis of ALS between January 2009 and January 2017. 92 patients met the inclusion criteria. We mainly verified three prognostic targets: (1) Time to non-invasive ventilation (NIV) or tracheostomy. (2) Time to percutaneous endoscopic gastrostomy or parental nutrition. (3) Survival. All EMG examinations were reviewed and a denervation score (DS) was calculated. The association of DS with clinical milestones was analysed, adjusting for disease duration, age, sex, and clinical phenotype. Results: We found a significant association between bulbar DS and time to NIV/tracheostomy (HR: 3.34, 95% CI: 1.49 to 7.48, p = 0.002) and with survival (HR 3.633, 95% CI 1.681–7.848, p = 0.001), regardless of the clinical phenotype. Furthermore, we found a significant influence of a general DS on survival (HR: 2.62, 95% CI 1.335–5.160, p = 0.005). Conclusion: EMG assessment could be of value not just for ALS diagnosis but also for its intrinsic prognostic value. Significance: EMG could provide additional information about the rate of progression of ALS as early as the diagnosis is made.